2019
DOI: 10.1080/10790268.2019.1656849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robotic-assisted gait training on the central vascular health of individuals with spinal cord injury: A pilot study

Abstract: Objective: To investigate the effect of a short-term, robotic-assisted (exoskeleton) gait training (RGT) program on central and peripheral hemodynamic measures in patients with spinal cord injury (SCI). Design: Parallel group, non-randomized trial with before (baseline) and after (follow-up) assessments. Setting: Single-center, community-based neuro-physiotherapy practice. Participants: Twelve individuals with SCI (ASI A to C). Interventions: Participants completed either a 5-day RGT program plus physiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Robotic exoskeleton-based gait training is reported to have a beneficial effect on cardiovascular health in individuals with SCI [ 20 ], a potential improvement of bone health [ 21 ], and psychological benefit [ 22 ]. Evidence is controversial for training-related improvement on independent gait function as measured by walking speed [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic exoskeleton-based gait training is reported to have a beneficial effect on cardiovascular health in individuals with SCI [ 20 ], a potential improvement of bone health [ 21 ], and psychological benefit [ 22 ]. Evidence is controversial for training-related improvement on independent gait function as measured by walking speed [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean pre-training blood pressure was 121/77 (SD = 1.43/7.4) mmHg, while the mean post-training blood pressure was 129/83 (SD = 4.09/7.4) mmHg. Faulkner et al conducted a pilot study on walking training assisted by an Ekso exoskeleton robot for the SCI population (Faulkner et al, 2019 ). The results showed that arterial wave reflection could be improved by a mean reduction of 9% and the training led to favorable changes in mean arterial pressure and central diastolic blood pressure, with mean decreases of 5 and 7 mmHg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The improvements observed in gait speed, walking distance and the E dimension of gross motor function, in comparison to CT, are clinically relevant regarding the personal autonomy of CP children. The RAGT physical exercise approach improves aerobic capacity and increases gait speed and walking distance [99], which allows for performing more activities of daily living requiring movement without getting tired and without needing so much assistance from relatives or caregivers. This meta-analysis provides relevant evidence regarding RAGT as the better therapeutic option, compared to CT, for the recovery of the gait speed and dynamic balance associated with locomotion.…”
Section: Discussionmentioning
confidence: 99%